2002
DOI: 10.1002/1521-3749(200211)628:11<2435::aid-zaac2435>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

The First [4+2]-Coordinated Tetraorganolead Compound: Synthesis, Structure and Conversion into a Triorganolead Cation, a Benzoxaphosphaplumbole, and Diorganolead Dihalides

Abstract: The syntheses and molecular structures, as determined by single-crystal X-ray diffraction analysis, of the first intramolecularly [4ϩ2]-coordinated tetraorganolead compound {4-t-Bu-2,6-[P(O)(OEt) 2 ] 2 C 6 H 2 }PbPh 3 (2) and the triphenyllead chloride adduct of the first intramolecularly coordinated benzoxaphosphaplumbole {[1(Pb),3(P)-Pb(Ph) 2 OP(O)(OEt)-5-t-Bu-7-P(O)-(OEt) 2 ]C 6 H 2 ·Ph 3 PbCl} (3a) are reported. The reaction of 2 with [Ph 3 C] ϩ [PF 6 ] Ϫ and p-MeC 6 H 4 SO 3 H, respectively, provides the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…The O(1)−Pb(1)−O(1B) angle of 149.5(1)° is close to the corresponding angle in the related heteroleptic stannylene {4‐ t Bu‐2,6‐[P(O)(O i Pr) 2 ] 2 C 6 H 2 }SnCl [O(1)−Sn(1)−O(2) 152.00(5)°]52 but much bigger than the O(1)−Pb(1)−O(2) of 119.36(5)° in the intramolecularly [4+2]‐coordinated tetraorganolead( IV ) derivative {4‐ t Bu‐2,6‐[P(O)(OEt) 2 ] 2 C 6 H 2 }PbPh 3 50. In contrast to related organosilicon( IV ),44−46 organotin( IV ),47−49 and organolead( IV )50 compounds containing the O,C,O‐coordinating ligand {4‐ t Bu‐2,6‐[P(O)(OR) 2 ] 2 C 6 H 2 } − (R = Et, i Pr), in the organoplumbylene 2 the P(O)(OEt) 2 groups and the lead atom are slightly displaced in the same direction from the plane defined by the aromatic ring [P(1)−C(2)−C(3)−C(4) = 177.5(3)°, Pb(1)−C(1)− C(2)−C(3) = 169.3(2)°]. The intramolecular Pb(1)−O(1) and Pb(1)−O(1B) distances of 2.518(2) Å are close to the intramolecular Pb−O [2.52(2) Å] reported for {2‐[Ph 2 P(O)CH 2 ]C 6 H 4 S} 2 Pb 53.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The O(1)−Pb(1)−O(1B) angle of 149.5(1)° is close to the corresponding angle in the related heteroleptic stannylene {4‐ t Bu‐2,6‐[P(O)(O i Pr) 2 ] 2 C 6 H 2 }SnCl [O(1)−Sn(1)−O(2) 152.00(5)°]52 but much bigger than the O(1)−Pb(1)−O(2) of 119.36(5)° in the intramolecularly [4+2]‐coordinated tetraorganolead( IV ) derivative {4‐ t Bu‐2,6‐[P(O)(OEt) 2 ] 2 C 6 H 2 }PbPh 3 50. In contrast to related organosilicon( IV ),44−46 organotin( IV ),47−49 and organolead( IV )50 compounds containing the O,C,O‐coordinating ligand {4‐ t Bu‐2,6‐[P(O)(OR) 2 ] 2 C 6 H 2 } − (R = Et, i Pr), in the organoplumbylene 2 the P(O)(OEt) 2 groups and the lead atom are slightly displaced in the same direction from the plane defined by the aromatic ring [P(1)−C(2)−C(3)−C(4) = 177.5(3)°, Pb(1)−C(1)− C(2)−C(3) = 169.3(2)°]. The intramolecular Pb(1)−O(1) and Pb(1)−O(1B) distances of 2.518(2) Å are close to the intramolecular Pb−O [2.52(2) Å] reported for {2‐[Ph 2 P(O)CH 2 ]C 6 H 4 S} 2 Pb 53.…”
Section: Resultsmentioning
confidence: 65%
“…Recently, we reported the arylbis(phosphonic) esters 5‐ t Bu‐1,3‐[P(O)(OR) 2 ] 2 C 6 H 3 ( A , R = Et; B , R = i Pr) and the application of their deprotonated monoanions to the synthesis of intramolecularly coordinated organosilicon( IV ),44−46 organotin( IV ),47−49 and organolead( IV )50 compounds, and of intramolecularly coordinated heteroleptic stannylenes 51. The latter, owing to intramolecular P=O⇄Sn coordination, show notably enhanced stability towards oxidation and thermal decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…They might serve as starting materials toward bismuth phosphonates following a simple synthetic approach described for metal(IV) phosphonates in which a metal(IV) halide is reacted with a phosphonic acid ester RPO(OR′) 2 under elimination of R′-X (DiGiacomo and Dines, 1981;Corriu et al, 1998;Guerrero et al, 2000). This concept was also shown to work for the synthesis of a variety of intramolecularly coordinated benzoxaphosphametallol derivatives such as [1(M),3(P)-M(R)OP(O)(OR′)-5-t-Bu-7-P(O)(OR′) 2 ]C 6 H 2 (M = Si, Sn, Pb, Bi; R = alkyl, aryl; R′ = Et, i-Pr) Peveling et al, 2001Peveling et al, , 2002Peveling et al, , 2004Peveling et al, , 2011. Previously, we have demonstrated that i-PrX elimination is observed upon thermal decomposition of monomeric bismuth complexes such as [BiX 3 L] 2 (X = Cl, Br, I; L = [(i-PrO) 2 (O) PCH 2 P(O)(Oi-Pr)] 2 ) accompanied by Bi-O-P bond formation Brought to you by | Western University Authenticated Download Date | 6/8/15 5:45 AM (Mansfeld et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Within our interest in hypercoordinated main group organometallic compounds containing the O,C,O -coordinating pincer-type ligands 4- t -Bu-2,6-[(RO) 2 P(O)] 2 C 6 H 2 – (R = Et, i -Pr) (Chart , d), so far we have investigated derivatives of silicon, a germanium, tin, , lead, , and antimony . A common feature of these compounds is, in an Arbuzov-type reaction, the elimination of alkyl halide under various conditions to afford intramolecularly PO→M coordinated phosphole-type compounds with, for instance, M = SiPh 2 , SnPh 2 , and PbPh 2 (Chart , e ).…”
Section: Introductionmentioning
confidence: 99%